Influence of vegetation type and season on rodent assemblage in a Mexican temperate forest mosaic - Flores-Peredo, Rafael; Vázquez-Domínguez, Guillermo (THERYA, 2016)
Knowing the factors that influence abundance, distribution and species richness is key to establish local conservation strategies. We evaluated the influence of vegetation type (pine, oak-alder-forest and grassland) and (dry, wet) season on the assemblage rodent in a mosaic of temperate forest in Mexico. The completeness of the inventory was evaluated by nonparametric estimators ACE and Jackknife. We use a generalized linear model to evaluate the effect of vegetation type, season and interaction (vegetation type*season) on the richness and abundance of rodents. The effect of factors and their interaction on the abundance of each species were evaluated with two-way analysis of variance with rank transformations. To analyze changes in the assembly structure we used rank-curves abundances and ANCOVA to assess differences in dominances/evenness of species. We found that rodents were more abundant in the pine forest and during the dry season, but the interaction between oak-alder forest and the dry season also favored abundance. At species level, Peromyscus melanotis was abundant in the pine forest and Reithrodontomys fulvescens in the oak-alder-forest. Between seasons, only the abundance of P. maniculatus was higher in the dry season than the wet season. The results show that mosaics with trees are of crucial importance for rodent’s conservation during the dry seasons.